Hepatic Chemerin and Chemokine-Like Receptor 1 Expression in Patients with Chronic Hepatitis C. (9th July 2014) - Kukla, Michał; Adamek, Brygida; Waluga, Marek; Zalewska-Ziob, Marzena; Kasperczyk, Janusz; Gabriel, Andrzej; Mazur, Włodzimierz; Sobala-Szczygieł, Barbara; Bułdak, Rafał J.; Zajęcki, Wojciech; Kępa, Lucjan; Ziora, Katarzyna; et al.
Abstract : Introduction . Chemerin seems to be involved in pathogenesis of chronic hepatitis C (CHC). Hepatic expressions of chemerin and its receptor, chemokine receptor-like 1 (CMKLR1), in CHC have not been studied so far. Aim . To evaluate chemerin and CMKLR1 hepatic expression together with serum chemerin concentration in CHC patients and to assess their relationship with metabolic and histopathological abnormalities. Methods . The study included 63 nonobese CHC patients. Transcription of chemerin and CMKLR1 was assessed by quantitative real-time PCR, while serum chemerin was assessed by enzyme-linked immunosorbent assay. Results . Expression of chemerin and CMKLR1 was present in the liver of all CHC patients regardless of sex or age. This expression was not associated with necroinflammatory activity and steatosis grade, fibrosis stage, and metabolic abnormalities. There was a negative association between serum chemerin and chemerin hepatic expression (r = (−0.41), P = 0.006). Conclusion . The study for the first time confirmed a marked expression of chemerin and CMKLR1 in the liver of CHC patients. The study was performed using the homogenates of human liver tissue, so it is not possible to define whether hepatocytes or other cell types which are abundantly represented in the liver constitute the main source of chemerin and CMKLR1 mRNA.